TOPORIŠIČEVO LETO (11. 10. 2015–11. 10. 2016) - Kus, Mateja; Majce, Irena (Slavia Centralis, 2020)
V prispevku je opisan potek aktivnosti, ki so se odvijale v Toporišičevem letu (11. 10. 2015–11. 10. 2016).